The Effect of the Position of the Pyridine Nitrogen Atom in the Tridentate NN'O Schiff Base Ligand on the Type of Coordination Polymer of the Copper(II) Complex: A Crystallographic Study - Kimia Forooghi; Hadi Amiri Rudbari; Reza Azadbakht (شیمی کاربردی روز, 2024)
Coordination polymers (CPs) are synthesized using bridging organic ligands and metal ions, depending on the geometric coordination of the metal, the bridging ligands, and the donor atoms present in these ligands, various one-, two-, or three-dimensional polymeric structures can form. To investigate the effect of the position of the pyridine nitrogen atom in the tridentate NN'O Schiff base ligand on the type of coordination polymers, two copper complexes were prepared. The ligand HL2 was characterized using IR, NMR, and elemental analysis, while the complexes were analyzed and identified using IR, elemental analysis, and X-ray diffraction techniques. The structural data of the copper complexes indicated that changing the pyridine nitrogen from position 3 to position 4 in the Schiff base ligand altered the structure of the copper complex from two-dimensional to three-dimensional. Analysis of inter- and intramolecular interactions using the NCI program shows that the interactions in both molecules are of the hydrogen bonding, halogen bonding, CH…π, π…π stacking, metal…π, and lone-pair…π type.